Product design why materials matter (TV Choice Production, 1989)
The design of a product is, of course, critical to its success. But a key part of any design is the choice of material to be used. Lifeboats, aeroplanes, even fillings for teeth - innovations in the use of materials have led to great advances and big profits. But how does a company set about making the choice of material to suit a particular design? This video explores this question through a case study of a company which makes cellular telephones